Collocation Methods for a Class of Volterra Integral Functional Equations with Multiple Proportional Delays (Advances in Applied Mathematics and Mechanics, 2012)
In this paper, we apply the collocation methods to a class ofVolterra integral functional equations with multiple proportionaldelays (VIFEMPDs). We shall present the existence, uniqueness andregularity properties of analytic solutions for this type of equations,and then analyze the convergence orders of the collocation solutionsand give corresponding error estimates. The numerical results verifyour theoretical analysis.